2018
DOI: 10.7897/2277-4343.09122
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Analysis of Phenolic Acids and Antioxidant Activity of Some Classical Ayurvedic Guggulu Formulations

Abstract: Classical guggulu formulations have been used as mainstay therapeutics in chronic inflammatory diseases in Ayurvedic system of medicine since centuries. The present study included six guggulu formulations such as Kaishora guggulu, Kanchanara guggulu, Yogaraj guggulu, Punrnava guggulu, Amritadi guggulu and Trayodasanga guggulu.Phenolic compounds play a vital role as evident from phenolic and flavonoid content in guggulu drugs as well as antioxidant activity assayed by DPPH radical scavenging activity and FRAP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…These are sub-classified as benzoic acid and cinnamic acid backbone structure containing seven (C6-C1) and nine (C6-C3) carbon atoms, respectively. Hydroxybenzoic acid derivatives such as gallic acid, syringic acid and cinnamic acid derivatives like caffeic acid, chlorogenic acid, sinapic acid, p-coumaric acid are widely available in plants 33 , 34 , 59 , 60 . Masek et al ., concluded that caffeic acid is the predominantly and widely available phenolic acid, and it exhibits antioxidant and iron-chelating abilities which are better than p coumaric acid 61 .…”
Section: Discussionmentioning
confidence: 99%
“…These are sub-classified as benzoic acid and cinnamic acid backbone structure containing seven (C6-C1) and nine (C6-C3) carbon atoms, respectively. Hydroxybenzoic acid derivatives such as gallic acid, syringic acid and cinnamic acid derivatives like caffeic acid, chlorogenic acid, sinapic acid, p-coumaric acid are widely available in plants 33 , 34 , 59 , 60 . Masek et al ., concluded that caffeic acid is the predominantly and widely available phenolic acid, and it exhibits antioxidant and iron-chelating abilities which are better than p coumaric acid 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the different phenolic acids and flavonols, OC contains a higher amount of Gallic acid and Kaempferol with respect to OS, as evident from chromatograms. Like other polyphenols, Gallic acid and Kaempferol can help to cure oxidative stressrelated diseases like diabetes and microbial pathogenesis [2]. They have anticancer activity.…”
Section: Fig 16 Overall Work Flow Of the Current Research Workmentioning
confidence: 99%
“…They contain a diverse range of chemical compounds of high therapeutic value. These phytochemicals such as polyphenols, flavonoids, tannins, alkaloids, and other organic components belongs to secondary metabolites of medicinal plants [1][2][3][4][5][6]. These compounds have a vital function in protecting us against infections and other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Kwas elagowy występował w produktach na poziomie około 5 mg/g, a kwas syringowy 2,5 mg/g. Pozostałe związki stwierdzono w znacznie niższym stężeniu (poniżej 1 mg/g produktu) [15].…”
Section: Kwasy Fenoloweunclassified